Genetic Diversity and Population Structure of Tetraploid Wheats (Triticum turgidum L.) Estimated by SSR, DArT and Pedigree Data. - Giovanni Laidò (PLoS ONE, 2013)
Levels of genetic diversity and population genetic structure of a collection of 230 accessions of seven tetraploid Triticum turgidum L. subspecies were investigated using six morphological, nine seed storage protein loci, 26 SSRs and 970 DArT markers. The genetic diversity of the morphological traits and seed storage proteins was always lower in the durum wheat compared to the wild and domesticated emmer. Using Bayesian clustering (K = 2), both of the sets of molecular markers distinguished the durum wheat cultivars from the other tetraploid subspecies, and two distinct subgroups were detected within the durum wheat subspecies, which is in agreement with their origin and year of release. The genetic diversity of morphological traits and seed storage proteins was always lower in the improved durum cultivars registered after 1990, than in the intermediate and older ones. This marked effect on diversity was not observed for molecular markers, where there was only a weak reduction. At K >2, the SSR markers showed a greater degree of resolution than for DArT, with their identification of a greater number of groups within each subspecies. Analysis of DArT marker differentiation between the wheat subspecies indicated outlier loci that are potentially linked to genes controlling some important agronomic traits. Among the 211 loci identified under selection, 109 markers were recently mapped, and some of these markers were clustered into specific regions on chromosome arms 2BL, 3BS and 4AL, where several genes/quantitative trait loci (QTLs) are involved in the domestication of tetraploid wheats, such as the tenacious glumes (Tg) and brittle rachis (Br) characteristics. On the basis of these results, it can be assumed that the population structure of the tetraploid wheat collection partially reflects the evolutionary history of Triticum turgidum L. subspecies and the genetic potential of landraces and wild accessions for the detection of unexplored alleles.